Interactive genre-based e-modules with flip pdf professional as a digital solution for teaching descriptive text - Azizul Maryati; Zulhermindra; Nina Suzanne; Rahmawati Rahmawati (University of Muhammadiyah Malang, 2025)
This study aims to develop a Genre-based approach E-Module for teaching descriptive text for grade XI senior high school students assisted by Flip PDF Professional application. Research and Development (R&D) design was used. The R&D model used in this study was the 4D model, which is divided into three steps: define, design, and develop. The instruments used were an interview guide, a students' need analysis questionnaire, and a validation sheet of the E-module. The collected data were analyzed by using descriptive qualitative method, a descriptive statistic, and a validation formula. The findings show that the students of grade XI in SMA N 2 Lintau Buo need to learn descriptive text clearly and structurally but struggle with vocabulary, grammar, and writing. The design of the developed Descriptive text E-module based on the Genre-based approach assisted by the Flip PDF Professional application consists of the cover, acknowledgment, table of contents, glossary, and introduction, which include learning objective, learning activities that follow the concept of Genre-based approach learning, evaluation, answer key and scoring guide, and bibliography, which all of this are structurally organized to make the students easy to follow the flow of the E-module. The validity score of the Descriptive text E-module based on the Genre-based approach assisted by the Flip PDF Professional application meets the “very valid” category with average of 89,01%.